Negotiating policy research, academic knowledge, and political movements: one researcher's experience - Upadhya, Carol (2008)
This paper reflects upon my recent experience in carrying out a policy-oriented research project on laws, policies, and practices related to land rights in Jharkhand. The research threw up issues that are empirically very complex and theoretically as well as politically sensitive, and raised questions about the production and uses of academic knowledge in the context of state-sponsored development-oriented research. This paper highlights concerns about the relationship between academic research and knowledge, politics, and policy-making, and points to broader questions about history, memory, and power in the context of adivasi autonomy movements. - Reproduced.
Keywords: Land tenure - India - Jhharkhand; Land tenure